Income Poverty in Nigeria: Incidence, Gap, Severity and Correlates - Edoumiekumo, Samuel Gowon; Karimo, Tamarauntari Moses; Tombofa, Steve S (American Journal of Humanities and Social Sciences, 2014)
<!--[if gte mso 9]> <![endif]--> This paper examined the incidence, depth and severity of poverty, and poverty correlates in Bayelsa state using the FGT decomposable class of poverty measures and a logit regression model as analytical tools on the 2009-10 NLSS data. Results from the FGT model showed that about 25 percent of households are income poor. To escape poverty the averagely poor has to mobilize financial resources to be able to meet 14 percent of N22393.62 household per capita expenditure monthly and the core poor has to mobilize financial resources up to 9 percent more of N22393.62 household per capita expenditure monthly than that required for the averagely poor. Results from the logit regression showed that agriculture and household size increases the probability that a household will be poor while dwelling in the urban area, being headed by male, a naira increase in households per capita expenditure on education and per capita expenditure on health and a year’s increase in the number of years spent schooling by household head reduces the probability that a household will be poor. However the major poverty correlates in Bayelsa state were found to be per capita expenditure on education, per capita expenditure on health, years of schooling and household size. It was therefore recommended that free, compulsory and quality education at least up to the basic level as being practiced in some states of the country, easily accessible and quality healthcare services be provided. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->